Relations between Biomechanical Parameters and Static Power of Arms in Children with Disturbed Posture - Slobodan Andrašić; Zoran Milić; Milan Cvetković; Darijan Ujsasi; Dejan Orlić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2017)
This study is aimed at determining the parameters and biomechanical analysis of their impact on the static arm strength in children with impaired posture as poor kyphotic posture, lordotic poor posture and children with flat feet. A transversal study included a sample of 67 children on the territory of the municipality of Subotica. The structure of the sample is as follows: 22 subjects with impaired kyphotic posture, 18 patients with impaired lordotic posture, and 27 subjects with flat feet. Measuring the level of static arm strength was done by the standardized "folding endurance" test. Observing the morphological development of children with kyphotic, lordotic poor posture and flat feet determined statistically significant differences in biomechanical variables.